ANALISIS KEMAMPUAN SOFT SKILLS SISWA KELAS XI SMK FUTUHIYYAH MRANGGEN DEMAK - Zam, Muh; Khoiriyyah, Kholifatul (Sains and Technology Faculty, Walisongo State Islamic University, 2018)
Learning in SMK should be able to equip the skills to students, especially soft skills skills to work in the world of work, so that learning is more meaningful and useful for students. The design of learning with chemoenterpreneurship approach should foster the soft skills of the students, so this research aims to map the students' soft skills ability in quantitative descriptive. Technique of taking data using non test in the form of soft skill observation sheet. The study was conducted on students of class XI SMK Futuhiyyah Mranggen Demak. The results show that soft skills include: solving problems with high criteria, communicating with high criteria, high criteria leadership, creative thinking with high criteria and teamwork with high criteria.